1987
DOI: 10.1111/j.2042-7158.1987.tb05131.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhein: an anthraquinone that modulates superoxide anion production from human neutrophils

Abstract: Rhein (4,5-dihydroxyanthraquinone-2-carboxylic acid), the active metabolite of diacetylrhein, which has been reported as an effective antirheumatic drug in man, inhibited superoxide anion production from human neutrophils challenged with N-formylmethionyl-leucyl-phenylalanine (FMLP: IC50, 2 x 10(-5) M) and A23186 (IC50, 10(-5) M), but not with phorbol myristate acetate. In the same concentration range (10(-6)-10(-3) M), the drug did not affect oxy-radical production by a cell-free hypoxanthine-xanthine oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 22 publications
(17 reference statements)
0
25
0
Order By: Relevance
“…Kimura et al (1981) reported that the active substances baicalin and baicalein from Scutellaria root decreased serum and liver lipid levels in hyperlipidemic rats. In addition, rhein and emodin, which are the active metabolites of rhubarb, inhibit lipid peroxide production and scavenge and/or inhibit hydroxyl radicals generated (Jung et al, 2004;Mian et al, 1987). Lin and Jin (1995) also reported that sennoside A isolated from rhubarb has regulatory free calcium functions in vivo, and has been observed to lower blood pressure and cholesterol levels.…”
Section: Introductionmentioning
confidence: 93%
“…Kimura et al (1981) reported that the active substances baicalin and baicalein from Scutellaria root decreased serum and liver lipid levels in hyperlipidemic rats. In addition, rhein and emodin, which are the active metabolites of rhubarb, inhibit lipid peroxide production and scavenge and/or inhibit hydroxyl radicals generated (Jung et al, 2004;Mian et al, 1987). Lin and Jin (1995) also reported that sennoside A isolated from rhubarb has regulatory free calcium functions in vivo, and has been observed to lower blood pressure and cholesterol levels.…”
Section: Introductionmentioning
confidence: 93%
“…23) Thus BOF containing Rhei Rhizoma 24) and Scutellariae Radix 25) may have atherosclerosis-preventive effect. The inhibitory actions of a Rhei Rhizoma component combined with BOF on nitric oxide 26) and superoxide anion, 27,28) the free radical-scavenging action of Scutellariae Radix, 29) and the scavenging actions of Angelicae and Paeoniae Radix on the superoxide anion and hydroxyl radical 30) are also considered to be involved in the inhibitory effects of BOF on intimal thickening.…”
Section: )mentioning
confidence: 99%
“…Rhein, a metabolite of anthranoids, is a major component of Rhei Rhizoma. The efficacy of rhein in the therapy of degenerative joint and bone diseases has been demonstrated in various clinical studies [8 -10] and may be mediated by the ability of rhein to restrict the migration of leukocytes into inflamed tissue and to reduce the superoxide anion production from human neutrophils [11], to inhibit the activity of several proteases [12], and to increase hyaluronate synthesis [13], as well as to increase the fluidity of lymphocyte membranes [14]. Emodin exists in numerous herb species, such as Rheum officinale Baill.…”
mentioning
confidence: 99%